Reimagining e+e− collider precision luminosity measurements - Wilson Graham; Madison Brendon (EPJ Web of Conferences)
Our recent work has shown that a novel much higher granularity forward calorimetry concept can enable much more detailed and precise reconstruction than the baseline designs based on LEP luminometers, along with the capability of electron/positron/photon separation. This new calorimeter concept is designed primarily to maximize the acceptance for e+e− → γγ as an alternative luminosity process, where it serves to define the inner edge of the acceptance (there is no outer edge, as the complete detector is used in the measurement), while continuing to provide the standard luminosity measurement from small-angle Bhabha scattering (SABS). It will also serve as a general forward electromagnetic calorimeter helping ensure hermeticity and detecting individual electrons, positrons, and photons. In this contribution we highlight the Bhabha rejection capability in the context of the e+e− → γγ luminosity measurement and motivate the utility of a Bhabha “mini-tracker” consisting of a few planes of upstream thin silicon detectors. This could further refine the e+/e− polar angle measurement, aid with charge measurement, improve Bhabha rejection (for γγ), and, last-but-not-least, help mitigate the beam-induced electromagnetic deflection that biases the Bhabha acceptance by providing high precision longitudinal vertex information in Bhabha events, which can be used to diagnose this effect of the beam on the final-state electron and positron.